Personal Hygiene Traders in the Central Market during the 2021 Covid-19 Pandemic - Hajrah Abdullah; Andi Susilawaty; Nurdiyanah Syarifuddin (Public Health Department, Universitas Islam Negeri Alauddin Makassar, 2021)
Personal hygiene is very important for traders to pay attention to in order to minimize contact and the possibility of transmission of the Covid-19 virus. This study aims to determine the personal hygiene of traders during the COVID-19 pandemic in 2021. The type of research used is a quantitative research with a descriptive approach. The population in this study were all traders in the Bulukumba Central Market with a total sample of 88 traders. The sampling technique used is random sampling technique. The results of this study indicate that the knowledge of traders about personal hygiene during the Covid-19 pandemic is in the good category, namely 97.7%, the attitude of all traders in the good category is 100%, the actions of traders in the good category are 85.2%. The results of this study also show that personal hygienewith good category as many as 52 respondents (59.1%). It is expected that traders will still have to comply with every government regulation in preventing Covid-19 by using masks, keeping a distance or social/physical distancing, applying cough etiquette, always washing hands using soap and running water, diligently cleaning or spraying disinfectants on frequently touched objects. , consuming nutritious food, and also the importance of accessing reliable sources of information about personal hygiene during the Covid-19 pandemic that is good and correct.